Alpha-synuclein targets GluN2A NMDA receptor subunit causing striatal synaptic dysfunction and visuospatial memory alteration - Durante, Valentina; de Iure, Antonio; Loffredo, Vittorio; Vaikath, Nishant; De Risi, Maria; Paciotti, Silvia; Quiroga-Varela, Ana; Chiasserini, Davide; Mellone, Manuela; Mazzocchetti, Petra; Calabrese, Valeria; Campanelli, Federica; et al. (Brain (London, England : 1878), 2019)
Parkinson's disease is a progressive neurodegenerative disorder characterized by altered striatal dopaminergic signalling that leads to motor and cognitive deficits. Parkinson's disease is also characterized by abnormal presence of soluble toxic forms of α-synuclein that, when clustered into Lewy bodies, represents one of the pathological hallmarks of the disease. However, α-synuclein oligomers might also directly affect synaptic transmission and plasticity in Parkinson's disease models. Accordingly, by combining electrophysiological, optogenetic, immunofluorescence, molecular and behavioural analyses, here we report that α-synuclein reduces N-methyl-d-aspartate (NMDA) receptor-mediated synaptic currents and impairs corticostriatal long-term potentiation of striatal spiny projection neurons, of both direct (D1-positive) and indirect (putative D2-positive) pathways. Intrastriatal injections of α-synuclein produce deficits in visuospatial learning associated with reduced function of GluN2A NMDA receptor subunit indicating that this protein selectively targets this subunit both in vitro and ex vivo. Interestingly, this effect is observed in spiny projection neurons activated by optical stimulation of either cortical or thalamic glutamatergic afferents. We also found that treatment of striatal slices with antibodies targeting α-synuclein prevents the α-synuclein-induced loss of long-term potentiation and the reduced synaptic localization of GluN2A NMDA receptor subunit suggesting that this strategy might counteract synaptic dysfunction occurring in Parkinson's disease.